« De la poésie polonaise » d’Auguste Lacaussade et Le cimetière du Père Lachaise de Juliusz Słowacki - Pawłowska, Maja (2022)
Auguste Lacaussade, in his article ‘De la poésie polonaise’, has identified the relevant features of Polish romanticpoetry: the originality and harmony of the language, the favourite themes (silence, shadow, ghosts, and the tendencyto rise above the real) and the fundamental dominants (mysticism, patriotism, suffering and the pain of expatriation).All of these elements can be found in the poem Le cimetière du Père Lachaise by Juliusz Slowacki. It is obvious thatthe French poet was able to reach a wider and more general point of view, but with a literary insight uncommon atthe time.
Keywords: Słowacki, Juliusz